Advances in organometallic chemistry. - Perez, Pedro J., 1965-; Stone, F. Gordon A.; West, Robert; Achard, Mathieu (Advances in organometallic chemistry, 2014)
This book contains authoritative reviews regarding the field of Organometallic Chemistry, written by highly qualified experts within the area, and reviewed by other experts before publication. Because of this high standard, AOC is one of the most cited journals in both Organic and Inorganic Chemistry fields.